PEMBELAJARANKEWIRAUSAHAANDARI PENGUSAHA YANG PERNAH MENGALAMI KEGAGALAN USAHA - Herjuno Tisnoaji; IJK Sito Meiyanto (Program Studi S1 Psikologi, 2019)
This study aims to understand what kind of entrepreneurial learning obtained by entrepreneurs after experiencing business failure and how they obtain such lessons. By understanding the essence of post-failure entrepreneurial learning, entrepreneurs would be able to acknowledge the insights gained by fellow failed entrepreneurs. In order to achieve that goal, a phenomenological study was conducted towards purposively-selected participants, namely entrepreneurs who had experienced failure from their businesses Data was collected using phenomenological semi-structured interview and analyzed using interpretative phenomenology analysis. This research shows that there are two types of lesson learned from business failure: 1) lesson about technical knowledge in how to manage business (which includess knowledge in financial management, marketing, and relationship management) and 2) lessons about personal growth (which includes detailed business planning and commitment in managing business). Moreover, entrepreneurs tend to learn from two sources; 1) personal reflection and 2) other entrepreneur, which includes entrepreneurial community and business mentors